2006
DOI: 10.1007/s00436-006-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Neospora caninum and bovine herpes virus 1 coinfection in cattle

Abstract: A seroprevalence survey of Neospora caninum and bovine herpesvirus 1 (BHV-1) was conducted in cattle pasturing in an area of the southern Italian Apennines to investigate the coinfection of these two pathogens. Blood samples were collected from 948 pastured cattle raised on 81 farms. Sera were tested for antibodies to N. caninum and to BHV-1 using an ELISA assay and a neutralization test, respectively. Out of the 81 farms sampled, 63 (77.8%) were positive for N. caninum and 80 (98.8%) for BHV-1. Coinfection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The seroprevalence (27.7%) in 3 counties (Arad, Bihor, and Timiş) was lower, however, than that previously reported in cattle with reproductive problems from dairy farms in central and northern regions of the country (55.9%; Gavrea and Cozma, 2010). Compared to several other European countries, our seroprevalence was higher than that reported in Slovakia (20.1%; Reiterová et al, 2009) and Hungary (2.5%; Hornok et al, 2006), similar to that found in the northwest of Spain (23.2%; Eiras et al, 2011) but lower than that reported in Italy (32.0%; Rinaldi et al, 2007) and Turkey (46.5%; Kul et al, 2009).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The seroprevalence (27.7%) in 3 counties (Arad, Bihor, and Timiş) was lower, however, than that previously reported in cattle with reproductive problems from dairy farms in central and northern regions of the country (55.9%; Gavrea and Cozma, 2010). Compared to several other European countries, our seroprevalence was higher than that reported in Slovakia (20.1%; Reiterová et al, 2009) and Hungary (2.5%; Hornok et al, 2006), similar to that found in the northwest of Spain (23.2%; Eiras et al, 2011) but lower than that reported in Italy (32.0%; Rinaldi et al, 2007) and Turkey (46.5%; Kul et al, 2009).…”
supporting
confidence: 74%
“…0.05) was found between the seroprevalence of N. caninum antibodies associated with the breed of the animals. Several studies have shown that dairy cattle are more susceptible to N. caninum than are beef cattle (Bartels et al, 2006;Hornok et al, 2006;Rinaldi et al 2007), and vice versa (Eiras et al 2011), but breed-related susceptibility to infection was not demonstrated; in addition, the role of farm dogs was not investigated in these studies.…”
mentioning
confidence: 91%
“…From this result it was assumed that risk factors supporting the introduction and spread of BVDV in cattle, such as high cattle density and frequent purchase of animals, also increase the risk of N. caninum infection. In an Italian study, a positive association between antibodies against bovine herpesvirus 1 (BHV-1) and antibodies against N. caninum was demonstrated (372). The possibility of whether BHV-1-induced immunosuppression after natural infection or vaccination could increase the susceptibility of cattle to secondary infection with N. caninum was discussed.…”
Section: Infection Riskmentioning
confidence: 99%
“…The possibility of whether BHV-1-induced immunosuppression after natural infection or vaccination could increase the susceptibility of cattle to secondary infection with N. caninum was discussed. However, to prove this hypothesis, experimental or follow-up studies after infection or vaccination are necessary (372). In a Canadian study of 78 dairy herds in Ontario, no significant association between antibodies against N. caninum and serostatus to Leptospira interrogans serovar Hardjo, Icterohaemorrhagiae, or Pomona was observed (343).…”
Section: Infection Riskmentioning
confidence: 99%
“…Finally, the possibility of infection with Neospora caninum, a common pathogen that causes similar fetal brain lesions (Fig. 1C, 1D) 15 and has been identified serologically in coinfections with BHV-1, 18 was investigated in all cases.…”
Section: Introductionmentioning
confidence: 99%